2018
DOI: 10.1111/echo.13832
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of Berry syndrome by fetal echocardiography: A report of four cases

Abstract: Berry syndrome is a rare congenital cardiac malformation. We describe 4 cases of Berry syndrome diagnosed by fetal echocardiography. Based on our experience, the three-vessel view is important for diagnosing the aortopulmonary window and aortic origin of the right pulmonary artery. Furthermore, the true cross-sectional and sagittal views obtained by continuously scanning from the three-vessel-trachea view to the long-axis view of the aortic arch are required to image the interruption or coarctation of the aort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Berry syndrome is an extremely rare disease, accounting for only 0.046% of all reported cases of congenital heart anomalies [52]. It is more common in males (67.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Berry syndrome is an extremely rare disease, accounting for only 0.046% of all reported cases of congenital heart anomalies [52]. It is more common in males (67.1%).…”
Section: Discussionmentioning
confidence: 99%
“…However this only amounted to 54 studies in total as some artices described different tests from the same study. Of the 134 indirect evidence papers or abstracts, 133 were synthesised41–174 as well as a single trial record 175. None of the seven included trials identified from trial registries reported interim or final results and only four remain active 176–179.…”
Section: Resultsmentioning
confidence: 99%
“…For both risk of bias and applicability to the review question, the majority (n=129) had some concerns,41 42 44–67 69–87 89–149 151–170 172–174 and five had a high level of concern43 68 88 150 171 (figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…This syndrome is named after Dr. Teresa E Berry, who and her colleagues from Chicago Memorial Children's Hospital first described this entity 2 . It is an extremely rare disease, accounting for only 0.046% of all reported cases of congenital heart anomalies 3 . It is more common in males (67.1%), presents commonly before 3 months with one or more clinical symptoms, including cyanosis, respiratory distress, cardiac murmur, symptoms of congestive cardiac failure, and other systemic symptoms 4 …”
Section: Case Reportmentioning
confidence: 99%
“…2 It is an extremely rare disease, accounting for only 0.046% of all reported cases of congenital heart anomalies. 3 It is more common in males (67.1%), presents commonly before 3 months with one or more clinical symptoms, including cyanosis, respiratory distress, cardiac murmur, symptoms of congestive cardiac failure, and other systemic symptoms. 4 The occurrence of an atrial septal defect in a patient with berry syndrome is extremely rare with only two patients reported out of 68 patients for whom details are available in the literature.…”
mentioning
confidence: 99%